2022
DOI: 10.1097/md.0000000000029565
|View full text |Cite
|
Sign up to set email alerts
|

Facial microbial flora in bearded versus nonbearded men in the operating room setting: A single-center cross-sectional STROBE-compliant observational study

Abstract: Beards are controversial in the operating room setting because of the possible retention and shedding of pathogens. Surgical site infection poses a significant burden on healthcare systems. All male healthcare workers who entered the operating room were approached to participate in the study. Four facial swab samples were anonymously collected and a hygiene practice questionnaire was administered. Sample A was taken from the upper and lower lips, sample B from cheeks, and samples C and D were collected by 20 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study by Wakeam et al 11 demonstrated that bearded healthcare workers do not harbor more virulent bacteria in their beards and, in fact, clean-shaven men were 10 percent more likely to harbor colonies of Staphylococcus aureus and more than three times as likely to be colonized with methicillin-resistant coagulase-negative staphylococci. Similarly, El Edelbi et al 12 has shown that non-bearded healthcare workers had a significantly higher bacterial load in their facial flora than their bearded counterparts. Moreover, men with beards have bacteria that has antibacterial activity that could inhibit the growth of Escherichia coli and Staphylococcus aureus 13 .…”
Section: Introductionmentioning
confidence: 94%
“…A study by Wakeam et al 11 demonstrated that bearded healthcare workers do not harbor more virulent bacteria in their beards and, in fact, clean-shaven men were 10 percent more likely to harbor colonies of Staphylococcus aureus and more than three times as likely to be colonized with methicillin-resistant coagulase-negative staphylococci. Similarly, El Edelbi et al 12 has shown that non-bearded healthcare workers had a significantly higher bacterial load in their facial flora than their bearded counterparts. Moreover, men with beards have bacteria that has antibacterial activity that could inhibit the growth of Escherichia coli and Staphylococcus aureus 13 .…”
Section: Introductionmentioning
confidence: 94%